Analisis Kemampuan Berpikir Kreatif Siswa Melalui Implementasi Pembelajaran Proyek Pembuatan Bel Listrik Sederhana - Rosyidah Ariani (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
Online learning of science subjects during a pandemic must still pay attention to intellectual abilities, namely the ability to think at a high level so that national education goals can be achieved, one of which is creative thinking. In this best practice, the results of learning innovations using project learning in making simple electric bells with the help of Canva by YPM 3 Taman Middle School students are used as material for analyzing students’ creative thinking abilities. This research involved 33 students of class IX-C at Senior High School YPM 3 Taman. The method used is a quantitative descriptive method. The research data were obtained from observations on the results of project reports from class IX-C students. Based on the observation results, it was found that the original thinking ability of 62.12% was in a good category; the ability to think flexibly by 78.79% is included in the good category; the ability to think smoothly by 56.82% is included in the sufficient category; and detailed thinking skills of 59.85% are included in the sufficient category. It can be concluded that the creative thinking skills of class IX-C students in learning the electric bell-making project assisted by Canva were 64.39% included in the good category.